Childhood contact with social services, self-harm and suicidal or self-harm ideation in young adulthood: a population-wide record-linkage study - S. McKenna; D. O’Reilly; E. Ross; A. Maguire (Epidemiology and Psychiatric Sciences)
Abstract Background Childhood contact with social services is associated with a range of adverse mental health outcomes across the life course, yet there is limited evidence in relation to self-harm and suicidal or self-harm ideation.